Privatisation and liberalisation in European telecommunications : comparing Britain, the Netherlands, and France - Hulsink, Willem (Routledge studies in international business and the world economy, 1999)
This book looks at comparative telecommunications regimes in the context of the EC. It analyzes individual policy management and change in three diverse regulatory cultures, namely Britain, the Netherlands and France.